Effect of Palm Oil Mill Effluent (POME) Treatment by Activated Sludge - Wun, Wee Long; Chua, Gek Kee; Chin, S. Y. (CleanWAS, 2017)
The objective of this study is to investigate the effect of operating conditions on palm oil mill effluent (POME) using activated sludge treatment. The operating conditions examined are initial pH, hydraulic retention time (HRT), organic loading rate (OLR), initial mixed liquor volatile suspended solids (MLVSS), solid retention time (SRT), and molasses concentration added as a carbon source. The efficiency of activated sludge was evaluated by treating the anaerobic treated POME under aerobic conditions based on the F/M ratio of 0.3 kg BOD/kg MLVSS.day. The best operating condition for initial pH, HRT, OLR, initial MLVSS, SRT, and molasses concentration were found to be 6.5 ± 0.1, 48 hours, 650 ± 20 mg/L, 2000 ± 200 mg/L, 10 days and 50 mg/L, respectively. However, the removal of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in POME ranging from 62 - 68% and 60 – 65% respectively for all best conditions. In fact, the removal of BOD still does not meet the Department of Environment (DOE)’s discharge standard limit of 20 mg/L. Therefore, further investigation and study of POME treatment need to be carried out in order to find a better solution to meet the DOE discharge standard.